Relationship between risk perception and occupational accidents: a study among foundry workers - Jafari, Mohammad Javad (J Egypt Public Health Assoc, 2019)
BACKGROUND: Risk perception is an effective factor in the determining of the incidence of unsafe behaviors and the occurrence of occupational accidents in the workplace. OBJECTIVE: The purpose of this study is to determine the relationship between risk perception and occupational accidents among foundry workers in Tehran, Iran. METHODS: In this cross-sectional study, all male workers in a foundry unit were initially selected (n = 245). After applying the study criteria and dismissing incomplete returned questionnaires, only 109 workers were included in the study. The General Health Questionnaire and the Flynn et al. Risk Perception Questionnaire were used to assess the mental health and risk perception of workers, respectively. Data regarding the occupational accidents of workers were also extracted from the accidents’ records of the foundry. Workers with a record of occupational accidents during 2013–2016 were compared with workers without an occupational accident record. RESULTS: Findings showed that a one-unit increase in the risk perception score resulted into an increase of approximately 33% in the odds of the occurrence of occupational accidents, but this rate was not significant (p = 0.695). In addition, the study found no significant relation between the risk perception score and the frequency of occupational accidents (Spearman’s r = 0.003, p = 0.977). CONCLUSION: There is no statistically significant relationship between risk perception and occupational accidents among foundry workers in Tehran, Iran.